In-vivo Intramuscular Collagen Synthesis, Muscle Fiber Growth and Histomorphology of Pectoralis major of a Fast-Growing Broiler Strain Gallus gallus domesticus - Pramir Maharjan; Casey M. Owens; Craig Coon (Frontiers in Veterinary Science, 2020)
Collagen protein has been considered as major culprit to myopathy condition affecting Pectoralis major, called woody breast (WB) in Gallus gallus domesticus (broiler). The WB myopathy is characterized by macroscopic stiffness of P. major and the affected tissue have reduced protein quality. This study measured the in-vivo soluble (S-) and insoluble (I-) collagen fractional synthesis and degradation rates (FSR and FDR) in P. major over typical grow-out cycle of broiler using stable isotope of 1-13C proline as metabolic tracer. Collagen content and muscle fiber histomorphology of P. major were also assessed simultaneously. The FSR and FDR for S- and I-collagen decreased over age, however FSR remained higher than FDR suggesting collagen was accreting during the grow-out period. This was reflected by increment in total collagen content in P. major in maturing broiler. Histomicrographs showed myodegeneration occurring as early as 21 days followed by greater accumulation of collagenous tissue in perimysial and endomysial connective tissue spaces of muscle fibers as bird aged. The findings suggest that reduced turnover of collagen in P. major at the later age of bird could have evolved due to adaptive physiological feedback mechanism against further synthesis and deposition of collagen in the extracellular matrix.